2015
DOI: 10.1016/j.schres.2015.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Auditory P3a and P3b neural generators in schizophrenia: An adaptive sLORETA P300 localization approach

Abstract: The present study investigates the neural substrates underlying cognitive processing in schizophrenia (Sz) patients. To this end, an auditory 3-stimulus oddball paradigm was used to identify P3a and P3b components, elicited by rare-distractor and rare-target tones, respectively. Event-related potentials (ERP) were recorded from 31 Sz patients and 38 healthy controls. The P3a and P3b brain-source generators were identified by time-averaging of low-resolution brain electromagnetic tomography (LORETA) current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 49 publications
4
32
0
Order By: Relevance
“…It is noteworthy that this filter was only applied to estimate the time window related to the EEG response. Thirdly, the maximum amplitude of the low‐pass filtered evoked wave in the Pz channel was located into a window ranging from 250 to 550 ms from the stimulus onset (Bachiller et al, ). The corresponding sample to the maximum amplitude was used as a central time sample of the response window.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that this filter was only applied to estimate the time window related to the EEG response. Thirdly, the maximum amplitude of the low‐pass filtered evoked wave in the Pz channel was located into a window ranging from 250 to 550 ms from the stimulus onset (Bachiller et al, ). The corresponding sample to the maximum amplitude was used as a central time sample of the response window.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of neural generators, the P1 and N1 predominately relate to activity in visual cortex and ventral temporal areas, whereas the candidate regions contributing to the P3b include frontal, parietal and tempooccipital regions (e.g. Bachiller, et al, 2015;Volpe, et al, 2007) although the exact regions remain a topic of debate. Fawns-Ritchie, et al (2019) reported that frontal and temporal cortical thinning is associated with cardiometabolic burden in a large UK sample; other studies have reported more widespread cortical thinning (Brundel, van den Heuvel, de Bresser, Kappelle, & Biessels;Chen, et al, 2015;Last, et al, 2007;Leritz, et al, 2011;Veit, et al, 2014;Walsh, Shaw, Sachdev, Anstey, & Cherbuin, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The group of schizophrenic patients had average age of 33.30 with standard deviation (Std) 9.52. The patients were diagnosed according to DSM-IV [25] and they were receiving a variety of standard neuroleptics medications at the time of recording.…”
Section: Acquisition Of Real Eeg Signalsmentioning
confidence: 99%
“…As far as cognitive impairment is often correlated with modifications in the P300, this wave can be used as a measure to evaluate the various treatments on cognitive functions. In this regard, researchers have suggested the use of P300 as a clinical marker and now a large body of clinical research in the brain function assessment has been devoted to extracting and characterizing the P300 [9].…”
mentioning
confidence: 99%